A Pragmatic Analysis of Antony’s Oration in Julius Caesar - Rasheed, Awham; Kalaf, Zidane (Al-Adab Journal, 2022)
The present study attempts a pragmatic analysis of Antony’s famous oration in Shakespeare’s Julius Caesar. It aims to identify which speech acts were employed in this oration for the end of achieving a high level of persuasion and, hence, characterizing Antony’s peculiar persuasive style. To achieve this objective, the study adopts a pragmatic analysis utilizing the speech act theory whereby all speech acts uttered by Antony were hand-picked and collated to represent the data of the study. In the analysis of the data, Searle’s (1969) model for categorizing speech acts was adopted to best reflect the speech acts that helped exhibiting the persuasive intent of the writer. Leech’s (1983) politeness principles are adopted to show how polite the characters to each other. The finding of the study shows that the role of speech acts for persuasive goals was vital. It can be concluded that speech acts such as declarations, commissives, directives, etc., were all employed to achieve this rhetorical intention, however, the speech acts of representative were the most significant to portray Antony’s peculiar persuasive style.